Internal soft-tissue anatomy of Cambrian 'Orsten' arthropods as revealed by synchrotron X-ray tomographic microscopy. - Mats E Eriksson (Public Library of Science (PLoS), 2012)
The world-famous 'Orsten' Konservat-Lagerstätte has yielded detailed information about Cambrian arthropods and their morphology. Internal organs or soft tissues have, however, rarely been reported, an obvious palaeobiological drawback. In this study, we employed synchrotron radiation X-ray tomographic microscopy (SRXTM) to study microscopic 'Orsten' arthropods from the Cambrian of Sweden: Skara minuta and two phosphatocopine species, Hesslandona sp. and Hesslandona trituberculata. This exceptionally high-resolution technique reveals internal organs or soft tissues that allow detailed comparison with equivalent structures in extant crustaceans and functional inferences to be made. The S. minuta specimen shows the digestive system and muscles that extend to the extremities. The slanting anterior portion of the head and anterior position of the mouth with a straight oesophagus suggest a primarily brushing and scraping way of feeding. The prominent head appendage muscles indicate muscle strength and good capacity for food manipulation. In the phosphatocopines the bulbous labrum is one of the most prominent morphological structures of the body. All specimens analysed reveal pairs of muscle bundles within the labrum. Based on comparisons with extant crustacean relatives, these muscles would fulfil the function of moving the labrum up and down in order to open the buccal cavity. The results of this pilot study demonstrate that there is still much to be learned about the 'Orsten' taxa.